An assessment of the Irish population for large-scale genetic mapping studies involving epilepsy and other complex diseases - CORVIN, AIDEN; GILL, MICHAEL; MORRIS, DEREK WILLIAMS; O'DUSHLAINE, COLM (Nature Publishing Group, 2008)
The recent completion of the International HapMap Project has rapidly advanced our understanding of linkage disequilibrium (LD) in the human genome. Today, tagging SNPs (tSNPs) can be quickly and easily selected and consequently HapMap data are regularly applied to both small- and large-scale genetic mapping studies. However, to correctly interpret the application of HapMap-derived tSNPs in a genetic mapping study, an understanding of how well HapMap data represents LD in the study population is critical. The Irish population had not previously been characterised in this way. Here, we do so using a set of 4424 SNPs selected from 279 candidate genes for epilepsy genotyped across 1118 healthy individuals from the Irish, British, Finnish and Australian populations. By considering the Irish population alongside surrounding European populations, our results confirm that the HapMap European-derived population accurately estimates patterning of LD in European descent populations. The Irish population appears notably well matched to the European HapMap population, and is markedly similar to the neighbouring British population. Although we were unable to detect significant substructure within the Irish population (a favourable result for genetic mapping), methods for controlling stratification should always be incorporated. This analysis therefore confirms that the genetic architecture of the Irish population is well suited to the study of complex traits and that tSNPs selected using the HapMap data can be confidently applied to the Irish population.
PUBLISHED
Keywords: genetic mapping, tagging SNPs, tag transferability, linkage disequilibrium, structure